Increased sperm aneuploidy in two male carriers of germline TP53 mutations - Paulasova, Petra; Diblik, Jan; Trkova, Marie; Macek, Milan; Sedlacek, Zdenek (Cancer genetics, 2011)
Li-Fraumeni syndrome is a rare autosomal dominant cancer predisposition syndrome characterized by a broad spectrum of tumors. The disorder is caused by germline mutations in the TP53 gene. We studied chromosomes in the sperm of two male carriers of TP53 mutations. We observed increased sperm aneuploidy, mainly concerning the gonosomes when compared to four normal male controls. This observation may correlate with the involvement of the p53 protein in spermatogenesis, with its role in aneuploidy in cancer, and with the occurrence of two cases of Turner syndrome in families with germline TP53 mutations reported in the literature.
Keywords: zárodečné mutace; dospělí; Tumor Suppressor Protein p53; heterozygot; Germ-Line Mutation; aneuploidie; spermie; hybridizace in situ; Adult; Spermatozoa; lidé; Heterozygote; Sperm Count; Male; Li-Fraumeni Syndrome; nádorový supresorový protein p53; In Situ Hybridization; Liův-Fraumeniho syndrom; mužské pohlaví; Aneuploidy; počet spermií; Humans